TOMATO HYBRIDS ON A LOW-VOLUME SUBSTRATE OF TRANSITIONAL TURNOVER IN DAGHESTAN'S INDUSTRIAL GREENHOUSES - P. M. Akhmedova; M. M. Daguzhieva (Овощи России)
The area of greenhouses in Dagestan currently  exceeds 220 hectares, most of which were built over the past 5 years and are high-tech facilities. The aim of our research was to identify highly productive tomato hybrids for growing in winter green-houses and to study the characteristics  of their growth and development in transitional turnover; determination  of the optimal time for sowing seeds and planting tomato seedlings  for transitional turnover; determination  of the level of accumulation of nitrates in the fruits of tomato, depending on the varietal characteristics and growing conditions. Experimental work was carried out in the greenhouse farm LLC Agro-AS, located in the Novolaksky district, p.  Novokuli (Novostroy)  is  a  suburb of Makhachkala.   It  has been established that when growing a tomato under conditions of a transitional culture under specific light conditions, the most expedient are the dates: sowing seeds in the first half of August, planting plants in the green-house in the first and second decade of September. Growing tomato plants during this period allows the plants to enter into the fruiting phase earlier and thereby form a larger number of fruits of greater mass as compared with the later sowing and planting dates. The highest yields were distinguished hybrids: Tomimaru  Mucho F1, Kyoto F1 (19.0 and 18.1 kg /  m2 ). The profitability of the production of hybrids was 70-100%.